Aesthetics of the Saur Matua Ceremony in Surabaya - Simanjuntak, Josia William (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This study aims to describe the aesthetic form of art in the Saur Matua ceremony in Surabaya, which is an important part of the Batak cultural tradition. The background of this research focuses on the importance of understanding how elements of art, such as music, dance, and cultural symbols, contribute to creating aesthetic value and spiritual meaning in urban contexts. The method used in this study is a qualitative descriptive approach, which involves collecting data through observation, interviews, and documentation to gain a deep understanding of the ritual practice. The results of the study show that the aesthetics in the Saur Matua ceremony reflect the harmony between Batak culture and the urban environment of Surabaya, and serve as a representation of the last respect that is full of spiritual meaning. Elements such as dance, traditional music, and ritual decorations not only create an atmosphere that favors reflection and reverence, but also communicate profound social and religious values. The aesthetics in the Saur Matua ceremony are not only related to visual beauty, but also include emotional and spiritual experiences that bring participants closer to their cultural values. This research makes an important contribution to understanding the role of art and aesthetics in death rituals, as well as how traditions can adapt in modern contexts.